2008
DOI: 10.1021/bi8003928
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Binding Affinities of PDZ Partners for CFTR: A Biochemical Basis for Efficient Endocytic Recycling

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR)1 is an epithelial chloride channel mutated in patients with cystic fibrosis. Its expression and functional interactions in the apical membrane are regulated by several PDZ (PSD-95, discs large, zonula occludens-1) proteins, which mediate protein-protein interactions, typically by binding C-terminal recognition motifs. In particular, the CFTR-associated ligand (CAL) limits cell-surface levels of the most common diseaseassociated mutant ΔF508-CFTR. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
225
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 105 publications
(237 citation statements)
references
References 55 publications
11
225
1
Order By: Relevance
“…However, other studies have shown that upstream residues can contribute to PDZ binding affinity [14]. Our hypothesis was that different C-terminal anchor sequences might have distinct upstream preferences, washing out signals in a global motif analysis.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…However, other studies have shown that upstream residues can contribute to PDZ binding affinity [14]. Our hypothesis was that different C-terminal anchor sequences might have distinct upstream preferences, washing out signals in a global motif analysis.…”
mentioning
confidence: 95%
“…As promising extensions or sequence modifications are identified, FP [14] assays are used to determine binding constants for all five PDZ domains of the CFTR trafficking system. Each modification is then evaluated for its contribution to the affinity for CAL and to the loss of affinity for the individual NHERF domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggested that TC10, a small Rho-GTPase interacting with CAL and inhibiting CFTR-CAL binding, increased CFTR expression at the plasma membrane (36). When NHERF1 was coexpressed with CAL, the inhibitory effect of CAL on CFTR surface expression was overcome (18). Purified GST-His 6 -S-CFTR protein (1 g) was incubated with purified His 6 -S-CAL protein (1 g), to which increasing amounts of His 6 -S-MAST205 protein were added.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, silencing of CAL has been shown to restore function to CFTR and rescue the mutant F508del-CFTR (14,16,17). The CAL-induced reduction in CFTR expression and distribution in cells can be restored by the overexpression of NHERF-1, acting through a competition mechanism for binding to the PDZ motif of CFTR (18). These findings suggest that CAL negatively regulates CFTR intracellular processing and trafficking.…”
mentioning
confidence: 94%